The Use Of Geostatistics In The Delineation Of Grade And Tonnages Of Underground Sandstone-Type Uranium Deposits - Harry M. Parker (Society for Mining, Metallurgy & Exploration, 1979)
Exploration for sandstone-type uranium ore bodies which will be exploited using underground mining techniques is usually executed in sequential fashion. Geostatistical methods can be used at the earliest exploration stages to design drilling programs which have a high probability of success in the location and delineation of mineable ore-grade mineralization, should such mineralization exist. In succeeding development stages, geostatistics may be used to outline and define the potential grade of reserves and to apply confidence limits on the grade estimation. Delineation of mineable reserves for mine planning requires extensive development drilling; using such drilling data geostatistical methods may be used to minimize the drilling needed to achieve a desired level of confidence in the calculation of mineable uranium ore grade and tonnage. Because sandstone-type uranium deposits tend to be pod-shaped and are generally aligned along a mineralized trend, this paper proposes a geostatistical method of calculating uranium ore reserves which accounts for this fact and predicts the area within a trend which is underlain by ore. This method uses an indicator value; that is, drill holes which contain mineable ore-grade intercepts are coded as 1, those that do not are coded 0. The indicator may be kriged over the mineralized trend to obtain an estimate of the area underlain by ore. The thickness and grade-thickness may be kriged, and the average ore grade may then be obtained by dividing grade-thickness by thickness, as is conventional for stratabound deposits. The mean grade is then multiplied by the kriged mean thickness to obtain an estimate of the volume, and thence tonnage, of mineable ore within the trend.